Exploring Interdisciplinary Approaches to Enhance Early Diagnosis and Treatment of Breast Cancer: Insights from Nursing, Medicine, Pharmacy Technician and Radiology - Mahdi Abdullah O Al Shammari (7), Nawaf Muneef M Al Shammari (8), Waleed Saleh J Al Masoud (9), Rawan Khaled A Al Fouzan (10), Nawaf Sanad Musad Almutiri (11), Salah Mohammed Mufleh Alrasheedi (12)., Abdulaziz Abdullah Alotaibi (1), Haifa Jarallah Aldhamadi (2), Ayat Mohammed Zain Shami (3), Bdoor Ahmed Salbookh (4), Fatemah Mohammad Alhejji (5), Adel Ahmed M Al Zuhair (6) (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Breast cancer is the most common cancer among women worldwide, with an estimated 2.3 million new cases diagnosed in 2020. Early detection through screening and timely treatment significantly improves survival rates, with a 5-year relative survival rate of 99% for localized breast cancer detected before it spreads.There is clear evidence that an interdisciplinary, team-based approach can lead to improved outcomes for patients with breast cancer. Early and accurate diagnosis, along with coordinated treatment planning and delivery, are critical yet often hampered without effective collaboration between healthcare disciplines. A literature search was conducted in PubMed, CINAHL, and Web of Science databases using search terms related to "breast cancer", "interdisciplinary collaboration", "multidisciplinary care", "diagnosis", "treatment", and relevant disciplines. A total of 35 relevant articles were identified and reviewed to identify current practices and research on collaborative models across the diagnostic and treatment continuum.